Prognostic Factors for Elderly Patients Treated With Stereotactic Body Radiation Therapy for Pancreatic Adenocarcinoma - Sutera, Philip A.; Bernard, Mark E.; Wang, Hong; Heron, Dwight E. (Frontiers in Oncology, 2018)
Introduction Pancreatic ductal adenocarcinoma (PDAC) commonly presents later in life with a median age at diagnosis of 70 years. Unfortunately, elderly patients are significantly underrepresented in clinical trials. Stereotactic body radiation therapy (SBRT) is a promising treatment modality in this population as it has demonstrated excellent local control with minimal toxicity. We aimed to determine prognostic factors associated with outcomes in elderly patients treated with SBRT. Materials and Methods Elderly patients older than 70 treated with SBRT for PDAC at our institution, from 2004-2014 were included. Our primary endpoints included overall survival (OS) and local-progression-free survival (LPFS). Secondary endpoints included regional-progression-free survival (RPFS), distant-progression-free-survival (DPFS) and radiation toxicity. Endpoints were analyzed with the Kaplan-Meier method. The association of these survival endpoints with risk factors was studied with Cox proportional hazards models. Results We identified 145 patients with 146 lesions of pancreatic adenocarcinoma with a median age at diagnosis of 79 (range, 70.1-90.3). SBRT was delivered to a median dose of 36 Gy (IQR 24-36). Surgical resection was performed on 33.8% of the total patients. Median follow-up was 12.3 months (IQR 6.0-23.3 months) and the median survival for the entire cohort 14.0 months with a 2-year OS of 27%. Multivariate analysis (MVA) demonstrated surgery [p=<0.0001, HR 0.29 (95% CI, 0.16-0.51)] and post-SBRT CA19-9 [p=0.009, HR 1.0004 (95% CI, 1.0002-1.0005)] significantly associated with overall survival. Recurrent lesions [p=0.0069, HR 5.1 (95% CI, 1.56-16.64)] and post-SBRT CA19-9 levels [p=0.0107, HR 1.0005 (95% CI, 1.0001-1.0008)] were significantly associated with local control on MVA. For the entire cohort, 4.1% experienced acute grade 2+ toxicity and 2% experienced late grade 2+ toxicity at 2 years. Conclusion This review demonstrates prognostic factors in elderly patients with PDAC treated with SBRT. We identified surgical resection and post-SBRT CA 19-9 as predictive of overall survival in this population. Additionally, we show low acute and late toxicity following SBRT in elderly patients.